Clinical presentation, management, and pathophysiology of neuropathic itch - Steinhoff, Martin; Schmelz, Martin; Szabó, Imre Lőrinc; Oaklander, Anne Louise (The lancet, 2018)
Summary: Unlike conventional itch, neuropathic itch develops in normal skin from excess peripheral firing or dampened central inhibition of itch pathway neurons. Neuropathic itch is a symptom of the same central and peripheral nervous system disorders that cause neuropathic pain, such as sensory polyneuropathy, radiculopathy, herpes zoster, stroke, or multiple sclerosis, and lesion location affects symptoms more than aetiology. The causes of neuropathic itch are heterogeneous, and thus diagnosis is based primarily on recognising characteristic, disease-specific clinical presentations. However, the diagnosis of neuropathic itch is challenging, different subforms exist (eg, focal vs widespread, peripheral vs central), and the mechanisms of neuropathic itch are poorly understood, resulting in reduced treatment availability. Currently available strategies include treating or preventing causal diseases, such as diabetes or herpes zoster, and topical or systemic medications that calm excess neuronal firing. Discovery of itch mediators such as gastrin releasing peptide, receptors (eg, neurokinin-1), and pathways (eg, Janus kinases) might encourage much needed new research into targeted treatments of neuropathic itch.
Gesehen am 14.04.2020